Fifth Percentile Cutoff Values for Antipneumococcal Polysaccharide and Anti-Salmonella typhi Vi IgG Describe a Normal Polysaccharide Response - Schaballie, Heidi; Bosch, Barbara; Schrijvers, Rik; Proesmans, Marijke; De Boeck, Kris; Boon, Mieke Nelly; Vermeulen, François; Lorent, Natalie; Dillaerts, Doreen; Frans, Glynis; Moens, Leen; Derdelinckx, Inge; et al. (Frontiers in Immunology, 2017)
Background Serotype-specific antibody responses to unconjugated pneumococcal polysaccharide vaccine (PPV) evaluated by a World Health Organization (WHO)-standardized enzyme-linked immunosorbent assay (ELISA) are the gold standard for diagnosis of specific polysaccharide antibody deficiency (SAD). The American Academy of Allergy, Asthma and Immunology (AAAAI) has proposed guidelines to interpret the PPV response measured by ELISA, but these are based on limited evidence. Additionally, ELISA is costly and labor-intensive. Measurement of antibody response to Salmonella typhi (S. typhi) Vi vaccine and serum allohemagglutinins (AHA) have been suggested as alternatives. However, there are no large cohort studies and cutoff values are lacking. Objective To establish cutoff values for antipneumococcal polysaccharide antibody response, anti-S. typhi Vi antibody, and AHA. Methods One hundred healthy subjects (10–55 years) were vaccinated with PPV and S. typhi Vi vaccine. Blood samples were obtained prior to and 3–4 weeks after vaccination. Polysaccharide responses to 3 serotypes were measured by WHO ELISA and to 12 serotypes by an in-house bead-based multiplex assay. Anti-S. typhi Vi IgG were measured with a commercial ELISA kit. AHA were measured by agglutination method. Results Applying AAAAI criteria, 30% of healthy subjects had a SAD. Using serotype-specific fifth percentile (p5) cutoff values for postvaccination IgG and fold increase pre- over postvaccination, only 4% of subjects had SAD. One-sided 95% prediction intervals for anti-S. typhi Vi postvaccination IgG (≥11.2 U/ml) and fold increase (≥2) were established. Eight percent had a response to S. typhi Vi vaccine below these cutoffs. AHA titer p5 cutoffs were ½ for anti-B and ¼ for anti-A. Conclusion We establish reference cutoff values for interpretation of PPV response measured by bead-based assay, cutoff values for S. typhi Vi vaccine responses, and normal values for AHA. For the first time, the intraindividual consistency of all three methods is studied in a large cohort.